If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.065x + 0.05(12 + -1x) = 0.10(-90) 0.065x + (12 * 0.05 + -1x * 0.05) = 0.10(-90) 0.065x + (0.6 + -0.05x) = 0.10(-90) Reorder the terms: 0.6 + 0.065x + -0.05x = 0.10(-90) Combine like terms: 0.065x + -0.05x = 0.015x 0.6 + 0.015x = 0.10(-90) Multiply 0.10 * -90 0.6 + 0.015x = -9 Solving 0.6 + 0.015x = -9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.6' to each side of the equation. 0.6 + -0.6 + 0.015x = -9 + -0.6 Combine like terms: 0.6 + -0.6 = 0.0 0.0 + 0.015x = -9 + -0.6 0.015x = -9 + -0.6 Combine like terms: -9 + -0.6 = -9.6 0.015x = -9.6 Divide each side by '0.015'. x = -640 Simplifying x = -640
| 88x^4/121x | | 6-3(4x-6)=-6 | | ln(x/y)-ln(10) | | ln(x/10*y) | | 2+7a=65 | | 5x-4=5(x-9) | | -4(x+8)=-44 | | p=a+3+c | | 5(w-4)=25 | | 4.1y=20.5 | | 10y-5=5y+5 | | 5b-6=8b | | 9x-9=40 | | -6x-14x=40 | | 5c-8c=21 | | 7a+2=26+39 | | 8x+9=2+6x+4 | | x-3y+3=0 | | 10+6x=-5x+21 | | -5x+2=5x+22 | | -5+7x=4x-8 | | -x+2=42-5x | | 3x^2-4x-319=0 | | -25x^2+36y^2=900 | | 3y+3=0 | | -3x^2+4x-319=0 | | tanx(tanx-1)=0 | | f(-1)=2x^2-20x+7 | | 4x+7=6x+13 | | -9(-3u^3+3-6y^2)= | | f(x)=-4x^2+5x+5 | | 0x+0y+0z=15 |